Altered permeability and beta-lactam resistance in a mutant of Mycobacterium smegmatis. - Mukhopadhyay, S (1997)
Beta-lactam resistance in mycobacteria results from an interplay between the following: (i) beta-lactamase production, (ii) affinity of the penicillin-binding proteins (PBPs) for the drugs, and (iii) permeation of the drugs. A laboratory mutant of Mycobacterium smegmatis was studied in order to evaluate the roles of these factors in beta-lactam resistance. Mutant M13 was between 7- and 78-fold more resistant than the wild type to cephaloridine, cefoxitin, cefazolin, cefamandole, and cephalothin. Increased beta-lactamase activity toward these antibiotics was not observed in the mutant. The PBP profiles of the wild type and M13 were comparable. However, the affinities of PBP 1 for the beta-lactams tested were lower for the mutant than for the wild type. The permeation of the drugs measured in intact cells was lower for M13 than for the parent strain. The liposome swelling technique, which could be used for cephaloridine, also supported this view. Reduced permeation was not restricted to the beta-lactams alone. Glycine uptake was also lower in M13. Taken together, the results suggest that decreased affinities of PBP 1 for beta-lactams, combined with the decreased permeability of the cell wall of the mutant, lead to the development of high-level acquired beta-lactam resistance.